Peningkatan Keterampilan Pemecahan Masalah Pengukuran Sudut melalui Penerapan Model Pembelajaran Problem Solving Learning (PSL) pada Peserta Didik Kelas IV Sekolah Dasar - Tri Kurnia Dewi; Chumdari Chumdari; Siti Kamsiyati (Universitas Sebelas Maret, 2019)
The direction of this research was to upgrade the problem solving skills of angular measurement by applying the problem solving learning (PSL) model in fourth grade students of public elementary school Tambakreja 02 Cilacap 2018/2019 academic year. This research was a classroom action research consists of 3 cycles with of 2 meetings. Every cycle consist 4 phases. The subjects of this research were 27 students and teachers.Data accumulating technique used interviews, observation, tests, and documentation. The data validity technique used source triangulation and technical triangulation. Data analysis technique maked use of critical analysis, descriptive comparative techniques, and interactive analysis models. The results showed that the average score of pre-action was 41.04 with classical completeness of 3.70%, increase in first cycle to 65,85 with classical completeness of 33,33%, increased at second cycle to 77,36 with classical completeness 66.67%, increased again in third cycle to 83,41 with classical completeness of 88.89%. Results of the research, it can be summarized that through the application of the problem solving learning (PSL) model can improve the problem solving skills of angular measurements in fourth grade student of SDN Tambakreja 02 Cilacap 2018/2019 academic year.Keyword: problem solving skills, problem solving learning model, angular measurement, and elementary school